Genesis of enhanced photoactivity of CdS/Ni-x nanocomposites for visible-light-driven splitting of water - Devi, Suman; Korake, Prakash V.; Achary, Srungarpu N.; Gupta, Narencira M. (International Journal of Hydrogen Energy, 2014)
A series of CdS/Ni-x nanocomposite photocatalysts, containing ca. 0.6-15 wt% Ni, were synthesized using a one-step hydrothermal method and characterized for their crystallographic, morphological, interfacial, and optical properties. Rietveld refinement of powder XRD data revealed the coexistence of wurtzite (hexagonal) and zinc blende (cubic) phases of CdS in ratios dependent on Ni content. Only a fraction of Ni existed as a secondary phase of NiS while the majority occupied the lattice positions of hexagonal CdS. Whereas up to 10-fold enhancement in H-2 evolution compared with pure CdS was observed for samples containing similar to 1.5-4.5 wt% Ni, samples with smaller or larger Ni content displayed poor activity for visible-light-induced splitting of water in presence of sulfide-sulphite ions as sacrificial electron donors. In contrary to recent findings, our study reveals that the enhanced CdS photoactivity is not a result of charge transfer between p-type NiS and n-type CdS, Ni-induced visible-region absorbance, or the coating of CdS particles by non-photoactive NiS. Instead, the preparation-dependent hexagonal/cubic CdS phase boundaries and particle morphology may play a crucial role. Additionally, certain Ni-doping-induced sub-bandgap shallow energy levels contribute to charge carrier separation. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: CdS/Ni-x nanocomposites; Dominant hexagonal facets; Enhanced photoactivity; Hydrogen evolution; Phase boundary effects; water splitting